An Analysis of Lecturers’ Competencies Based on Students’ Perceptions: A Mixed Methods Approach - Sudama, I Made; Adnyana, I Wayan Diana Putra (Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to evaluate lecturer competencies at Universitas Primakara based on student perceptions, addressing the need for enhanced teaching quality in Indonesian higher education amid global competitiveness demands. Employing a mixed-methods convergent parallel design, data were collected from 268 students using a four-point Likert-scale questionnaire assessing pedagogical, professional, social, and personal competencies, supplemented by open-ended responses for qualitative insights. Quantitative results indicate high competency ratings, with professional (mean = 3.80, SD = 0.45) and personal (mean = 3.70, SD = 0.48) domains leading, followed by social (mean = 3.60, SD = 0.52) and pedagogical (mean = 3.55, SD = 0.50). Qualitative themes reveal strengths in subject mastery and integrity but highlight needs for innovation in teaching methods, practical relevance, and digital engagement. These findings contribute to the field by integrating student perspectives into a comprehensive competency model, supporting Outcome-Based Education (OBE) implementation. Implications include targeted professional development in project-based learning and digital tools, offering a practical framework for improving lecturer training and aligning with global educational standards.